Association of Renal Resistive Index, Renal Pulsatility Index, Systemic Hypertension, and Albuminuria with Survival in Dogs with Pituitary-Dependent Hyperadrenocorticism - Hung-Yin Chen; Yu-Hsin Lien; Hui-Pi Huang (International Journal of Endocrinology)
An increased renal resistive index (RI) and albuminuria are markers of target organ damage secondary to systemic hypertension. This study evaluated associations between systemic blood pressure (SBP), renal RI, pulsatility index (PI), and albuminuria in dogs with pituitary-dependent hyperadrenocorticism (PDH). Predictors of overall mortality were investigated. Twenty client-owned dogs with PDH and 20 clinically healthy client-owned dogs as matched controls were included. Incidence rates of systemic hypertension (SBP ≥ 160 mmHg), albuminuria, and increased renal RI (≥ 0.70) and PI (≥ 1.45) in the control group were 5%, 0%, 5%, and 0%, respectively, compared to 35%, 40%, 50%, and 35%, respectively, in the PDH group (P=0.001, P<0.001, P<0.001, and P=0.001, resp.). No association between systemic hypertension, renal RI, renal PI, and albuminuria was observed. PDH was the only predictor of albuminuria and increased renal RI. Survival was not affected by increased renal PI, systemic hypertension, or albuminuria. Increased renal RI (≥ 0.70) was the only predictor of overall mortality in dogs with PDH.